Referral pattern of periodontal disease among general dental practitioners in iraq - Ali, Banaz Jabbar; Alwan, Alyamama Mahmood; Ali, Chinar Jabbar (Brazilian Dental Science, 2020)
Objectives: To evaluate the type of “periodontal treatment” performed by general dental practitioners and the referral patterns of periodontists in Iraq. Material and methods: A total of 201 general dentists were asked to complete a self-administered questionnaire consisting of nine questions regarding periodontal treatment and the referral patterns of periodontists. Results: The study showed that 91.1% of general dental practitioners (GDPs) performed “phase-I therapy”, and most of them done “scaling”. Regarding surgical periodontal therapy, only 12.9% of them performed surgical periodontal therapy, half of the GDPs did gingivectomy, and less than 30% performed crown lengthening. When evaluating maintenance therapy after periodontal treatment, it was found that 77.9% of the GDPs scheduled appointments for patients in the maintenance phase, 49.4% of them after one month, 24.7% after three months, and 15.6% after six months. Using TRUF analysis, most general dentists believed that the patient and periodontal factors were responsible for the recurrence of periodontal disease. Conclusions: There is still a lack of awareness of periodontal surgical procedures among the “general dental practitioners”. Thus, it is essential to increase the comprehension of periodontal treatment among general dentists. KEYWORDS Periodontal treatment; Phase-I therapy; Surgical periodontal treatment; General dental practitioner; Referral pattern Attitude.